Serum osteocalcin levels are inversely associated with UACR in Chinese DKD patients: a meta-analysis of 20 clinical studies - Hu, Xiaolan; Wang, Xiyu; Cai, Chen; Guo, Jiachen; Qian, Xin; Yu, Jiangyi; Huang, Liji; Xie, Shaofeng (Frontiers in Endocrinology, 2024)
Objective: To systemically assess the relationship between serum osteocalcin levels and the progression of diabetic kidney disease (DKD) in the Chinese population. Methods: The PubMed, Web of Science, CNKI, Wanfang Database, VIP and Chinese Medical Journal full-text Database were searched. Two investigators independently reviewed the literature and extracted data based on predetermined inclusion and exclusion criteria. The Newcastle-Ottawa scale was used to assess the quality of the literature. The statistical analysis was performed using Stata16 software. Results: A total of 20 case-control studies encompassed 4565 cases, consisting of 643 healthy controls (CN), 1 649 individuals with simple diabetes mellitus (DM), 1 305 with microalbuminuria (MI), and 968 with macroalbuminuria (MA). The meta-analysis results indicated that the serum osteocalcin levels in MI group were significantly lower than that in CN group and DM group [SMD = -1.15, 95% CI (-1.46, -0.85), P < 0.01; and SMD = -0.53, 95% CI (-0.69, -0.37), P < 0.01, respectively], and lower in the MA group compared to the CN group [SMD = -1.28, 95% CI (-1.79, -0.76), P < 0.01]. In the MA group, the serum osteocalcin levels were considerably lower compared to that in DM group and MI group [SMD = -0.93, 95% CI (-1.28, -0.58), P < 0.01; and SMD = -0.41, 95% CI (-0.65, -0.17), P < 0.01, respectively]. Conclusion: The serum osteocalcin levels are typically reduced and show a negative correlation with the severity of proteinuria in Chinese patients with DKD. This indicates a decline in bone formation at early-stage in DKD patients, which worsens as the disease progresses. Systematic review registration: https://www.crd.york.ac.uk/PROSPERO/, identiﬁer CRD42024580324.